IoT Safe Security System Using Voice Command and GPS Tracking: Sistem Keamanan IoT yang Aman Menggunakan Perintah Suara dan Pelacakan GPS - Dwi Arifianto; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Theft remains a significant security issue, requiring improved protection systems for valuable assets. Specific Background Conventional safe security methods, including mechanical locks and password systems, present limitations in usability and vulnerability to unauthorized access. Knowledge Gap Existing systems lack integrated solutions that combine voice-based control and real-time location monitoring within a single IoT framework. Aims This study aims to design and develop a safe security system using Google Voice Assistant and GPS tracking integrated with IoT technology. Results The system utilizes an ESP32 microcontroller, solenoid door lock, and Neo-6M GPS module, enabling voice-controlled access and real-time location monitoring via the Blynk application. Testing shows successful operation with voice command delays around 1–3 seconds and effective monitoring over distances ranging from 1 to 18 km. Network performance improvements were observed, with signal range increasing from 2 meters to 3 meters. Novelty The integration of Google Voice Assistant with IoT-based GPS tracking provides a unified approach for access control and location monitoring. Implications This system offers practical support for remote security management and contributes to the development of smart security technologies. Keywords: IoT Security, Safe System, Voice Command, GPS Tracking, ESP32 Key Findings Highlights Voice-based access control operates with consistent response timing Location monitoring supports long-distance tracking via mobile devices Network optimization shows measurable improvement in signal range